ИДЕНТИТЕТОТ ВО РОМАНИТЕ ЗА КРАЛЕ МАРКО НА СЛОБОДАН МИЦКОВИЌ И НА ВЛАДИМИР ЛЕВЧЕВ - Darin Angelovski (Philological Studies, 2019)
The text “Identity in the Novels about Krale Marko by Slobodan Mickovikj and Vladimir Levchev” discusses the role of literature as a kind of imaginary construction whilst understanding the historical past and a national history through the processes of self-identification and social identification. By employing the personage of Krale Marko as a figure of memory the two authors express a direct an interest for local traditions through an actualisation of the historic past in their respective societies (Macedonia and Bulgaria). Regarding the question of identity as a social construct, the analysis will show that said processes, as well as the process of collective identification, are dependent on literary and historical discourses by which every individual and society creates an image of the self.